THE SEALING SURFACE STRESS OF TUBING JOINTS HAS BEEN MODELED TO REFLECT WEAR. (International Journal of Food and Nutritional Sciences, 2022)
stress distribution on the sealing surface and propose a new method for determining joint wear that makes use of the numerical cutting technique. A three-dimensional model of a worn tubing junction subjected to complex stresses was created and validated using the finite element method in order to ascertain the stress distribution on the sealing surface. The failure mechanism of a worn tubing connection and the effects of interior wear on the joint were revealed by the examination of the stress distribution on the sealing surface. The results showed that the contact stress of the worn part of the sealing surface reduced as the internal wear depth increased. When the internal wear depth reaches 3.0 mm, the maximum contact stress in the worn region is 27.3% lower along the circumferential direction of the sealing surface and 35.5% lower in the axial direction compared to an unworn joint. The joint's sealing surface stress distribution is nearly equal to a new joint when the joint's outside wear is 3.0 mm or less. Because internal wear has a bigger influence on the sealing surface's stress qualities than external wear, controlling internal wear during operation is therefore more crucial than preventing external wear. The sealing belt is centered on the sealing surface and has a relatively constant width throughout two wear types and a wide variety of wear depths. By doing this, the tubing junction seal's quality is preserved.